Diabetes management in Wolcott-Rallison syndrome: analysis from the German/Austrian DPV database - Alena Welters (Orphanet Journal of Rare Diseases, 2020)
Abstract Background Wolcott-Rallison syndrome (WRS) is characterized by permanent early-onset diabetes, skeletal dysplasia and several additional features, e.g. recurrent liver failure. This is the first multicentre approach that focuses on diabetes management in WRS. We searched the German/Austrian Diabetes-Patienten-Verlaufsdokumentation (DPV) registry and studied anthropometric characteristics, diabetes treatment, glycaemic control and occurrence of severe hypoglycaemia (SH) and diabetic ketoacidosis (DKA) in 11 patients with WRS. Furthermore, all local treatment centres were personally contacted to retrieve additional information on genetic characteristics, migration background and rate of consanguinity. Results Data were analysed at diabetes onset and after a median follow-up period of 3 (1.5–9.0) years (time from diagnosis to latest follow-up). Median age at diabetes onset was 0.2 (0.1–0.3) years, while onset was delayed in one patient (aged 16 months). Seventy percent of patients manifested with DKA. At follow-up, 90% of patients were on insulin pump therapy requiring 0.7 [0.5–1.0] IU of insulin/kg/d. More than two third of patients had HbA1c level ≥ 8%, 40% experienced at least one episode of SH in the course of the disease. Three patients died at 0.6, 5 and 9 years of age, respectively. To the best of our knowledge three patients carried novel mutations in EIF2AK3. Conclusion Insulin requirements of individuals with WRS registered in DPV appear to be comparable to those of preschool children with well-controlled type 1 diabetes, while glycaemic control tends to be worse and episodes of SH tend to be more common. The majority of individuals with WRS in the DPV registry does not reach glycaemic target for HbA1c as defined for preschool children (< 7.5%). International multicentre studies are required to further improve our knowledge on the care of children with WRS.